Preface to the study of Paul - Westerholm, Stephen, 1949- (Grand Rapids, MI Eerdmans, 1997)
Includes bibliographical references and index.
Keywords: Bible. N.T. Romans -- criticisms,interpretations,etc; Paul, the Apostle, Saint; Bible. N.T. Epistles of Paul -- study and teaching